Analysis of agricultural labor efficiency from the perspective of labor productivity - Alesandra Marina Manolache; Alina Mărcuţa; Ionut Laurentiu Petre (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The approach regarding the efficiency of the labor force in agriculture, but also from the perspective of labor productivity in this sector, is determined by the economic activities for the development of the national economy. This paper is based on the comparative analysis of statistical data from a quantitative and qualitative point of view, highlighting labor productivity and labor resource consumption for the main activities of the national economy. For this research were identified statistical data provided by the National Institute of Statistics, data on the value of production, production costs, and the level of labor. With the help of these data, relating the value of production and production expenditures to the volume of labor, it was possible to determine two indicators that can be used to analyze the economic efficiency of labor, namely labor productivity and labor consumption. These two indicators were determined for the main branches of the national economy, implicitly also of the agricultural sector. Agriculture is considered one of the most powerful forces shaping human behavior and therefore economic activity. This paper investigates the effects of agriculture on labor productivity and the agricultural labor force that drive this relationship and are determined by the main activities of the national economy.
Keywords: Q10; Q15; 330; labor force; agriculture; labor productivity; economic efficiency